Arquitetura híbrida baseada em business process management, arquitetura corporativa e mineração de processos para apoiar o mapeamento e redesenho inteligente de processos organizacionais - Romero, Marcio (2021)
Making a digital transformation means integrating technology into the business, which requires fundamental changes in company culture, operations, and processes. This transformation requires that processes start to be mapped and redesigned in an intelligent way, since traditional methods are based on rigid and controlled steps, while the intelligent one is based on flexibility and adaptability to strategies. In this context, finding a solution that enables the intelligent mapping and redesign of processes becomes a challenge, as traditional methods such as Business Process Management, Enterprise Architecture and Process Mining are not intended to handle different views and are focused only on process management, IT infrastructure and information discovery in event logs. Given this scenario, developing a Hybrid Architecture that brings together these methods has become an important object of study to analyze the contribution of their combination. Thus, this work aimed to develop and apply a Hybrid Architecture based on Business Process Management, Enterprise Architecture with TOGAF and Process Mining to support the Intelligent Mapping and Redesign of Organizational Processes. The methodological characterization was applied in nature, with a quantitative and exploratory approach through bibliographical and experimental research. The computational experiments were developed in four phases with ten steps: selection of companies, selection of data, computational experiments, and comparison of results. Three databases from a company operating in the financial sector, another in health and the third from an academic study were used. In the selected processes of the first two companies, the separate BPM, TOGAF and Process Mining methods were applied, and in the third only Process Mining for control. Then, the Hybrid Architecture was applied in the second company and then compared with the results of the experiments, it was confirmed that the traditional methods are not as comprehensive as the Hybrid Architecture. In this comparison, it was possible to verify that Hybrid Architecture was more effective, as the time for mapping had a 60% reduction compared to the traditional method, 50% in the number of people involved and 20% in the return time. It is concluded, therefore, that the Hybrid Architecture, in addition to being unprecedented, also contributed to the achievement of the proposed objective, allowing the mapping and intelligent redesign of organizational processes, which brought intelligence and agility, in addition to the discovery of non-perceivable knowledge with other methods.